Intense pustular reaction during treatment of actinic keratosis with ingenol mebutate - Jaśkiewicz-Nyckowska, Dorota; Lewicka-Potocka, Zuzanna; Szczerkowska-Dobosz, Aneta (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Actinic keratosis is a common diagnosis in dermatological practice. Lesions usually appear on senile skin or skin exposed to sunlight. As they can progress to squamous cell carcinoma, all lesions should be properly treated. Ingenol mebutate is one of the newest topical agents. Objective. To present a severe site reaction during treatment of actinic keratosis with ingenol mebutate gel. Case report. An 85-year-old patient was treated with ingenol mebutate for an actinic keratosis lesion on the head. After the third day of treatment a massive local reaction was observed, with numerous pustular lesions. It was treated with a topical antibacterial agent. Complete remission of actinic keratosis was observed one month later. Conclusions. Treatment of actinic keratosis with ingenol mebutate carries the risk of local adverse effects, including severe pustular reaction. Patients should always be informed about possible side effects of the treatment and their transient nature.